CERTAIN CHRONO-BIOLOGICAL CHARACTERISTICS OF SEVERE ROAD TRAFFIC ACCIDENTS IN THE REGION OF PLOVDIV, REPUBLIC OF BULGARIA - Marin Baltov (Science & Research)

(untitled)
Over the last years, with the increase of the number of transportation vehicles, road traffic has become heavier and the number of incidents involving vehicles has been rising. The main causes of these incidents are motor vehicle drivers, whose behaviour is also influenced by factors of the environment. OBJECTIVE: To examine the influence of seasons, months and days of the week on the number of victims of road traffic accidents. MATERIAL AND METHOD: The object of this study are the cases of fatality in road traffic accidents in the region of Plovdiv over the period 2000-2014, registered and autopsied at the Department of Forensic Medicine of St. George University Multi-Profile Hospital for Active Treatment EAD, Plovdiv. Historical, statistical and graphic analysis methods have been used in the processing of the results. RESULTS: A total of 1288 cases of fatality in road traffic accidents in the region of Plovdiv over the period 2000-2014 were studied. It was found that the number of fatalities during the period ranges from 8.7%ооо to 15.43%ооо. This result is nearly twice as high as the result for the Republic of Bulgaria. The largest number of severe road accidents with deaths occur in the autumn (28.66%), and the risk months during the year are November, July and September. During the week, the number of victims increases from Monday and reaches its maximum on Sunday. The largest number of victims is registered in the second ten-day period of the month. CONCLUSION: The conclusions made regarding the influence of climatic and time factors on the number of severe traffic accidents can be used to optimise the measures for their prevention.